If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + h + -9 = 12 Reorder the terms: 23 + -9 + h = 12 Combine like terms: 23 + -9 = 14 14 + h = 12 Solving 14 + h = 12 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + h = 12 + -14 Combine like terms: 14 + -14 = 0 0 + h = 12 + -14 h = 12 + -14 Combine like terms: 12 + -14 = -2 h = -2 Simplifying h = -2
| 7x+6x-42=105-8x | | 3(4w-1)-5=10 | | -3/10=x-7/8 | | 9x-9=2+10x+12 | | 6x(x+1)=x+4 | | 3x^3-1=0 | | 2(a-5)-3(6a-3)=79 | | 7xy-4x^2y-2xy= | | 3(3x+5)=9 | | -1b-1b=9-8+3 | | 8(7-4)=38 | | 87-3x=-13 | | 0.5(2x+.75)-.75(0.1+x)=1 | | 0.24=30d | | 30k+60=20k+90 | | 2x^4-10x^2+12=0 | | 2.5+6=4.5y-1 | | r^2+2r-168=0 | | -10x+19+6x=59-5x | | 8x^2-9=6x | | 1.2(2t-3)=2.3(t-1) | | a+10=21 | | 3x^2-5b+2=0 | | 14=6x | | 0.2(60)+0.05x=0.01(60+x) | | 5a+2a+3a-3= | | y+(3y+3)=-9 | | 5z-2=17 | | 1+10x=5(2x+2) | | 4x-1-6x+7=11x+3-10x | | 9-8+3=s | | 194-3x10=0 |